2018
DOI: 10.20344/amp.9457
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de Vida das Crianças com Otite Média e Impacto da Colocação de Tubos de Ventilação Transtimpânicos numa População Portuguesa

Abstract: RESUMOIntrodução: A qualidade de vida é uma medida importante de avaliação de resultados em saúde. Embora a otite média seja uma das doenças mais comuns na infância, o seu impacto na qualidade de vida das crianças portuguesas não é conhecido. O objetivo deste estudo é determinar a qualidade de vida das crianças portuguesas com otite média crónica com efusão e/ou otite média aguda recorrente e o impacto a curto-prazo da colocação de tubos de ventilação transtimpânicos, utilizando a versão portuguesa do question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…It also found that HRQOL was more limited in children with bilateral hearing loss than those with unilateral hearing loss. It has been stressed in other studies that children having cochlear implants were found to have similar HRQOL to healthy children [51][52][53][54][55]. Changes in hearing threshold and tinnitus severity after stapes surgery have also been found to be important to quality of life in adult patients [56].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It also found that HRQOL was more limited in children with bilateral hearing loss than those with unilateral hearing loss. It has been stressed in other studies that children having cochlear implants were found to have similar HRQOL to healthy children [51][52][53][54][55]. Changes in hearing threshold and tinnitus severity after stapes surgery have also been found to be important to quality of life in adult patients [56].…”
Section: Discussionmentioning
confidence: 96%
“…then the local symptoms reported include: changes in breathing pattern to mouth breathing (adenoid faces/long face syndrome), malocclusion, altered voice timbre, night snoring, and night apnea. Furthermore, an enlarged adenoid may impair the patency of the Eustachian tube which, inter alia, can lead to exudative otitis media, that may lead to hearing loss [49][50][51][52][53][54][55]. Symptoms of tonsil hypertrophy are snoring, obstructive sleep apnea syndrome, speech disorders such as slurred speech, and dysphagia (especially with solid foods) [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]51,55].…”
Section: Discussionmentioning
confidence: 99%
“…Dentro desses parâmetros, é conveniente destacar métodos de avaliação que analisem as condições em que a criança se encontra, como questionários, que contribuem para a construção de um diagnóstico e um plano de cuidado efetivo no que tange às questões de saúde mental, especificamente. (LAMEIRAS et al, 2018) Relacionando a qualidade de vida com a saúde dentro das escolas, torna-se válido considerar as condições de vida dos indivíduos, sendo a instituição de ensino, um importante mecanismo de promoção à saúde. Tendo em vista a desigualdade social persistente no âmbito da educação em saúde, tanto em escolas particulares e públicas, existem indivíduos com semelhantes aspectos biopsicossociais, como os sentimentos depressivos e de estresse, que se agravam com o avanço da idade, aumentando sua vulnerabilidade.…”
Section: Qualidade De Vidaunclassified
“…The modest reduction in incidence of AOM with tympanostomy tubes [9][10][11] is enhanced by their other positive effects-decreased severity of AOM symptoms, improved diagnosis of AOM (no drainage, no infection), and sparing of systemic antibiotics thanks to effective ototopical treatments. Quality-of-life improvement 12,13 must be weighed against the known risks of surgery and general anesthesia. 14…”
Section: What Is Recurrent Acute Otitis Media?mentioning
confidence: 99%